2005
DOI: 10.1111/j.1471-4159.2004.02915.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome inhibition protects HT22 neuronal cells from oxidative glutamate toxicity

Abstract: Oxidative stress caused by glutathione depletion after prolonged exposure to extracellular glutamate leads to a form of neuronal cell death that exhibits morphologically mixed features of both apoptosis and necrosis. However, specific downstream executioners involved in this form of cell death have yet to be identified. We report here that glutamate exposure does not activate caspase-3 in the HT22 neuronal cell line. Furthermore, no cytoprotection was achieved with either the pan-caspase inhibitor Z-VAD-fmk or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 33 publications
(75 reference statements)
7
57
1
Order By: Relevance
“…These results are consistent with previous observations in other cell types, indirectly suggesting that disruption of redox homeostasis could be important in determining proteasome inhibitor effectiveness (Emanuele et al, 2002;Ling et al, 2003;Fribley et al, 2004;van Leyen et al, 2005;Pei et al, 2004;Minami et al, 2005). This effect might be related at least in part to the cell types analysed, as in other studies, antioxidants have been shown not to protect from bortezomib-mediated cell death, while ascorbic acid protection was due to direct binding to bortezomib (Zou et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with previous observations in other cell types, indirectly suggesting that disruption of redox homeostasis could be important in determining proteasome inhibitor effectiveness (Emanuele et al, 2002;Ling et al, 2003;Fribley et al, 2004;van Leyen et al, 2005;Pei et al, 2004;Minami et al, 2005). This effect might be related at least in part to the cell types analysed, as in other studies, antioxidants have been shown not to protect from bortezomib-mediated cell death, while ascorbic acid protection was due to direct binding to bortezomib (Zou et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…This provides an explanation of how tBHQ restrains AIF-mediated apoptosis under glutamate toxicity. Consistent with previous reports, no significant activation of caspase-3/7 was observed during glutamate-induced oxidative toxicity (Tan et al, 1998;van Leyen et al, 2005;Zhang and Bhavnani, 2006). Caspase activation during the initiation of apoptosis requires ATP (Li et al, 1997a;Hu et al, 1999;Fukui et al, 2009 reported that the lack of caspase-3/7 activation may result from rapid onset of mitochondrial dysfunction and energy depletion induced by glutamate.…”
Section: Discussionsupporting
confidence: 80%
“…This neural cell line was chosen because HT-22 cells are a well-characterized model of neural oxidative injury (30,46). These cells undergo oxidative stress-induced toxicity upon exposure to glutamate, which blocks glutamate-cystine antiporters in the plasma membrane, resulting in GSH deficiency and oxidative cell death (46). HT-22 cells were maintained in DMEM with glutamine, supplemented with 10% fetal bovine serum and penicillin=streptomycin (0.2%).…”
Section: Protein Extract Preparationmentioning
confidence: 99%